STRATEGI PERTEMPURAN RADEN MAS SAID DI VORSTENLANDEN: SIKAP PATRIOTISME DALAM MENEGAKKAN KEADILAN - Kuncoro Catur Setyo Atmojo; Nushrotul Khofifah; Devi Nur Maharani (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Raden Mas Said is a figure known in the Javanese saga as a figure who knows no fear. This figure once challenged three forces at once, namely the Surakarta Sunanate, the Dutch colonial, and the Yogyakarta Sultanate. The purpose of this study was to determine the fighting strategy of Raden Mas Said and his attitude towards the Kartasura Palace. This study uses the historical method with books, journals, and oral sources. The results of this study indicate that the battle strategy of Raden Mas Said is like eating jenang cartel porridge from the new edge to the middle, fighting from the new edge to the core and also using the Chakra Byuha battle title tactics which relies on its unity so as not to break and crush everything in its path. In front of him. This research is to complete.Keywords: Dutch Colonia; Struggle; Raden Mas Said.